2013
DOI: 10.1002/lary.24239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nasal sprays and irrigations in the delivery of topical agents to the olfactory mucosa

Abstract: Compared to sprays, irrigations provide a more effective method of delivering topical agents to the posterior and superior aspects of the nasal cavity. The thorough distribution of irrigations has important clinical implications for improving the delivery of therapeutic agents to the olfactory mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…In recent years, nasal irrigation have played a significant role in the medical management of CRS and other sinonasal disorders. The efficacy of nasal irrigations is likely explained by their ability to effectively distribute topical agents to the sinonasal cavities, remove debris and secretions from these areas, and ultimately enhance mucociliary clearance and nasal patency . Saline solutions in both hypertonic and isotonic formulations are commonly employed as topical therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, nasal irrigation have played a significant role in the medical management of CRS and other sinonasal disorders. The efficacy of nasal irrigations is likely explained by their ability to effectively distribute topical agents to the sinonasal cavities, remove debris and secretions from these areas, and ultimately enhance mucociliary clearance and nasal patency . Saline solutions in both hypertonic and isotonic formulations are commonly employed as topical therapies.…”
Section: Discussionmentioning
confidence: 99%
“…irrigations is likely explained by their ability to effectively distribute topical agents to the sinonasal cavities, remove debris and secretions from these areas, and ultimately enhance mucociliary clearance and nasal patency. 19,28,29 Saline solutions in both hypertonic and isotonic formulations are commonly employed as topical therapies. Although strong evidence exists regarding the efficacy and safety of saline irrigations to improve subjective and objective measures of nasal function, the use of nasal irrigations to affect olfactory performance has not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This focused dose will have the benefits of quicker onset of action, lower systemic side effects, and being more efficacious at lower doses. 46,47 More and more studies have demonstrated that the dosage at the diseased site, rather than the total dose, should be used as the predictor of clinical outcomes. 48 In addition, the initial site of drug deposition has an important effect on its bioavailability and associated therapeutic effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Balata et al [5] investigated propolis organogel as a novel topical delivery system for treating wounds. Topical delivery systems are employed not only to treat skin related problems, but also for complications associated with eyes, [6] nose, [7], vagina [8], or rectum [9] etc. where patients compliance and satisfaction are essential.…”
Section: Introductionmentioning
confidence: 99%